Short communicationCatheter inside the right heart for 22 years: to intervene or not to intervene? - Çimen, Tolga; Doğan, Mehmet; Akyel, Ahmet; Yeter, Ekrem (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Treatment of a central venous catheter emboli that has been asymptomatic for a number of years is controversial. A 56-year-old male patient who had an operation for sinus Valsalva aneurism rupture 22 years ago was referred to cardiology department for routine control. He had a mass inside the right heart on echocardiographic examination, and computed tomography revealed that this mass was an embolic piece of catheter. Catheters that have stayed inside the heart for a long time are removed due to the risk of distal embolisation and endocarditis, but the risk of removal is not known. Non-invasive follow-up of asymptomatic patients is often preferred because of the stabilisation of the embolised catheter due to endothelisation and the risk of complications during removal. Treatment of patients with catheter-piece emboli who are asymptomatic should be individualised, taking into account the risk of thrombosis, arrhythmia, and infection.